Decolonizing trauma studies: Trauma and postcolonialism - Andermahr, Sonya (MDPI AG - Multidisciplinary Digital Publishing Institute, 2016)
This Special Issue aims to explore the complex and contested relationship between Trauma Studies and postcolonial theory, focusing on the possibilities for creating a decolonized trauma theory that takes account of the suffering of minority groups and non-Western cultures, broadly defined as cultures beyond Western Europe and North America. The issue builds on the insights of, inter alia, Stef Craps's book, Postcolonial Witnessing, and responds to his challenge to interrogate and move beyond a Eurocentric trauma paradigm.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; discours dominant; décolonialisme; périodes historiques; ressource en ligne; système colonial; systèmes d'oppressions; trauma

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences